Thermal evaluation of self-rewetting fluids in server-grade heat pipes - Ya-Lin Hsiao; Chen-li Sun (Case Studies in Thermal Engineering)
This study investigates the feasibility of using self-rewetting fluids (SRWFs) in server-grade heat pipes with bent and flattened geometries, common in air-cooled thermal modules for data centers. Conventional fluids like water often face performance limitations at high heat loads, prompting interest in SRWFs that leverage inverse Marangoni convection for improved thermal performance. We experimentally tested aqueous solutions of 2-butanol (2–6 wt%), heptanol (0.05–0.1 wt%), and octanol (0.03 wt%). A 2–4 wt% 2-butanol solution achieved the highest cooling capacity, up to 70 W, a 9.1–27.3 % improvement over water. At 60–70 W, strong inverse Marangoni flow promoted effective liquid return to the evaporator, lowering the overall thermal resistance to 0.32–0.35 °C W−1. However, excessive concentrations (6 wt%) led to higher phase-change resistance and condenser flooding. Dilute heptanol and octanol solutions reduced overall thermal resistance by up to 14.9 % at moderate heat loads (30–50 W), benefiting from lower threshold temperatures for self-rewetting behavior. Optimal performance was observed at a 50° inclination, where both gravity and inverse Marangoni effects contribute synergistically. These findings highlight the importance of tailoring SRWF type and concentration to specific cooling demands and demonstrate the potential of SRWFs for improving performance, reliability, and design flexibility in commercial server cooling applications.